Sobre superfícies imersas em 3-variedades de contato homogêneas e construção de quase solitons de Ricci - (:unkn) unknown (Universidade Federal do Amazonas, 2016)
In the first part of this thesis, we calculate the Gaussian curvature of surfaces isometrically immersed in homogeneous contact Riemannian 3—manifolds in terms of mean curvature and contact angle. Moreover, we find the Laplacian of the contact angle and, as an application, we characterize Hopf 's torus as the unique connected and compact surface in the class of homogeneous and simply connected 3—manifolds with isometry group of dimension 4 which has both constant mean curvature and contact angle. Furthermore, we present sufficient conditions to isometrically immerse surfaces in these 3—manifolds. In the second part, we present necessary and sufficient conditions for warped product to admit the structure of gradient almost Ricci soliton. Besides that, some results about existence and rigidity are presented.
Keywords: Ângulo de contato; Variedade Homogênea; Curvatura Gaussiana; Produto warped; Quase soliton de Ricci; CIÊNCIAS EXATAS E DA TERRA: MATEMÁTICA